Tidal current at Songkla lagoon inlet - Kathirgamanathan, Murugesu; Suphat Vongvisessomjai; Tawatchai Tingsanchali; Nishimura, Hitoshi; The Government of United Kingdom (Bangkok : Asian Institute of Technology, 1976)
A tidal mathematical model was developed for the Songkla lagoon inlet, Thailand. Due to the tidal fluctuations, the flow in the inlet channel was unsteady. The node and branch method of computation was used in constructing the model. The governing equations of the unsteady flow were linearized and a computer program was developed to solve the linearized equations. The model was calibrated using the short measurement period of data available. The boundary conditions required for the model were the water stages at both end of the channel. The current velocities were predicted for a 4 months period using the data of the boundary conditions and calibrated Mannings' coefficient. Harmonic analysis was done for water stage and current velocity data using the parameters obtained from the analysis, the current velocity was predicted using the data of water level fluctuation. The results from the both methods are compared with measured values. Al though the node and branch method was originally used in channel networks, it is found to be applicable to the tidal flow calculations, in which the flow is actually not unidirectional. This method gives reasonably good results when the data of the boundary conditions are accurate.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Ocean currents -- Songkla lagoon